Twenty Years at Hull House; with Autobiographical Notes - Addams, Jane, 1860-1935 (Salt Lake City, UT : Project Gutenberg, 1998)
"Twenty Years at Hull-House; with Autobiographical Notes" by Jane Addams is an autobiographical account written during the early 20th century. The book chronicles Addams$1 (Bs experiences at Hull-House, a settlement house in Chicago, where she and her colleagues worked to improve the lives of local residents through social reform and community involvement. Addams reflects on her upbringing, her motivations for social work, and the challenges she faced as she interacted with the immigrant communities in Chicago. At the start of the book, Addams provides insight into her early life, emphasizing the strong influence her father had on her understanding of morality and responsibility. She shares vivid childhood memories that shaped her worldview, including her first encounters with poverty and the importance of honesty. Each anecdote not only frames her character development but also hints at her future endeavors at Hull-House, where the lessons learned in her youth will manifest in her commitment to social justice and community service. The beginning sets a reflective tone, revealing the personal struggles and motivations that would drive Addams to become a pivotal figure in the settlement movement and advocate for social change. (This is an automatically generated summary.)s
Release date is 1998-05-01
Keywords: Women social reformers -- United States -- Biography; Addams, Jane, 1860-1935; Hull House (Chicago, Ill.) -- History; Social service -- Illinois -- Chicago -- History; Social settlements -- Illinois -- Chicago -- History